1998
DOI: 10.1128/jb.180.12.3209-3217.1998
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Comparison of fliC Genes and Identification of Glycosylation in the Flagellin of Pseudomonas aeruginosa a-Type Strains

Abstract: Pseudomonas aeruginosa a-type strains produce flagellin proteins which vary in molecular weight between strains. To compare the properties of a-type flagellins, the flagellin genes of severalPseudomonas aeruginosa a-type strains, as determined by interaction with specific anti-a monoclonal antibody, were cloned and sequenced. PCR amplification of the a-type flagellin gene fragments from five strains each yielded a 1.02-kb product, indicating that the gene size is not likely to be responsible for the observed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Sixty‐seven of 123 (55%) keratitis isolates did not show hybridisation for either marker pKL‐1 or pKL3 compared to 122 of 322 (38%) nonkeratitis isolates ( P = 0.05). P. aeruginosa a‐type flagellins vary because of the presence of a glycosylation island (Brimer & Montie, ; Arora et al ., ) that can be present as either a longer insert encompassing 14 ORFs, or as a shorter version with a 5.4‐kb deletion (Arora et al ., ). Twenty of 123 (16%) keratitis isolates carried the full length glycosylation island (12 of 63 isolates in 2003–2004 and 8 of 60 isolates in 2009–2010) and 61 of 123 (50%) carried the truncated version.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty‐seven of 123 (55%) keratitis isolates did not show hybridisation for either marker pKL‐1 or pKL3 compared to 122 of 322 (38%) nonkeratitis isolates ( P = 0.05). P. aeruginosa a‐type flagellins vary because of the presence of a glycosylation island (Brimer & Montie, ; Arora et al ., ) that can be present as either a longer insert encompassing 14 ORFs, or as a shorter version with a 5.4‐kb deletion (Arora et al ., ). Twenty of 123 (16%) keratitis isolates carried the full length glycosylation island (12 of 63 isolates in 2003–2004 and 8 of 60 isolates in 2009–2010) and 61 of 123 (50%) carried the truncated version.…”
Section: Resultsmentioning
confidence: 99%
“…Brimer and Montie [33] demonstrated that type A, but not type B, £agellins are glycosylated but the structure of the glycosylation has not yet been de¢ned. Flagella of P. aeruginosa primarily consist of a FliC (£agellin) subunit.…”
Section: Flagellin Glycosylation Genes (Pak)mentioning
confidence: 99%
“…Genomic diversity resulting from horizontal gene transfer suggests a possibility of acquisition of novel virulence traits in P. aeruginosa. For example, flagella of some P. aeruginosa strains are often glycosylated (85). Very recently, it has been reported (77) that another genomic island of ca.…”
Section: Genetic Diversity and Genomic Islandsmentioning
confidence: 99%